2017
DOI: 10.3389/fnhum.2017.00384
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity Affects Entrainment of EEG in Music Listening

Abstract: Music perception involves complex brain functions. The relationship between music and brain such as cortical entrainment to periodic tune, periodic beat, and music have been well investigated. It has also been reported that the cerebral cortex responded more strongly to the periodic rhythm of unfamiliar music than to that of familiar music. However, previous works mainly used simple and artificial auditory stimuli like pure tone or beep. It is still unclear how the brain response is influenced by the familiari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Meltzer et al ( 2015 ) reported that the cerebral cortex induced a stronger response to the periodic rhythm of unfamiliar music than to that of familiar music. Furthermore, in a previous study, we reported a stronger response to unfamiliar music than to familiar music (Kumagai et al, 2017 ). Familiarity has also been studied extensively in research on visual perception.…”
Section: Introductionmentioning
confidence: 52%
“…Meltzer et al ( 2015 ) reported that the cerebral cortex induced a stronger response to the periodic rhythm of unfamiliar music than to that of familiar music. Furthermore, in a previous study, we reported a stronger response to unfamiliar music than to familiar music (Kumagai et al, 2017 ). Familiarity has also been studied extensively in research on visual perception.…”
Section: Introductionmentioning
confidence: 52%
“…Our previous work [22] showed that the cross-correlation function averaged across trials, channels, and participants, showed a pronounced peak. At the peak, the cross-correlation magnitudes while participants listening to unfamiliar and scrambled music were significantly larger than they were while listening to familiar music [22].…”
Section: B Feature Extractionmentioning
confidence: 92%
“…Moreover, cortical entrainment to the envelope of speech can be seen even at the single-trial level [19], [20]. Cortical entrainment to the music has also been demonstrated in terms of music perception [21], [22].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations